Operations, Quality, and Profitability in the Provision of Banking Services - Soteriou, Andreas; Zenios, Stavros A. (Management Science, 1999)
We develop a framework for combining strategic benchmarking with efficiency benchmarking of the services offered by bank branches. In particular, a cascade of efficiency benchmarking models is developed guided by the service-profit chain. Three models—based on the nonparametric technique of Data Envelopment Analysis—are developed in order to implement the framework in a practical setting: (i) an operational efficiency model, (ii) a service quality efficiency model, and (iii) a profitability efficiency model. The use of the models is illustrated using data from the branches of a commercial bank. Empirical results indicate that we gain superior insights by analyzing simultaneously the design of operations together with the quality of the provided services and profitability, rather than by benchmarking these three dimensions separately. Relationships are also established between operational efficiency and profitability, and between operational efficiency and service quality.